2015
DOI: 10.1109/tdmr.2015.2443055
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Evaluation of Nanoscale Silver Sintered Power Modules for Automotive Application Based on Experiments and Finite-Element Modeling

Abstract: Thermomechanical behavior of power modules has always been an issue regarding reliability improvement. Silver sintering technology is one of the few alternatives for dieattachment, which could bring longer operating lifetime. Finite Elements Modeling (FEM) is as much critical as experimental development for such a new technology. In this paper, we present a lifetime evaluation approach for power modules used in automotive applications thanks to thermal characterizations, thermal ageing and thermomechanical FEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…This method has been used for a very wide range of analysis. Many different geometries can be modeled using the method such as very complex parts of engineering systems [9][10][11][12][13][14][15], beams, plates [16], shells [17,18], human body parts such as kidney, bone etc. [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used for a very wide range of analysis. Many different geometries can be modeled using the method such as very complex parts of engineering systems [9][10][11][12][13][14][15], beams, plates [16], shells [17,18], human body parts such as kidney, bone etc. [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the improvement in lifetime performance of silver sintered joints compared to solder joints [45]- [48].…”
Section: A Component Reliability -Power Module Levelmentioning
confidence: 99%
“…However, Ag is a relatively expensive metal and most Ag pastes require the application of mechanical pressure-assisted sintering to ensure high-reliability bonding. [5,6] This constraint may increase the cost of power module assembly, cause chip damage, and consequently reduce yield and throughput when compared with a pressureless die-bonding process.…”
Section: Introductionmentioning
confidence: 99%